Recycling method of polyethylene glycol terephthalate (PET)
By using organic acids to catalyze the hydrolysis reaction of PET and polymerizing the hydrolyzed products with monomers, the existing PET recycling and utilization methods are solved, and the efficient preparation of PET hydrolysis and biodegradable copolyesters is achieved, simplifying the process and reducing costs.
Patent Information
- Application Number
- CN202411656923.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-19
AI Technical Summary
The existing PET recycling and utilization methods have problems such as complex processes, high energy consumption and separation and purification processing, making it difficult to achieve simple and low energy consumption PET recycling.
The organic acid adipic acid, lactic acid and/or glycolic acid are used as catalysts to carry out PET hydrolysis reaction. The hydrolysis product does not need to be separated and is directly used for subsequent polymerization reactions. The biodegradable copolyester is prepared by adding different monomers.
It realizes efficient hydrolysis of PET, simplifies the process flow, reduces the generation cost, and converts non-degradable PET into biodegradable copolyesters, alleviating environmental pollution problems.
Smart Images

Figure BDA0005142311140000031 
Figure BDA0005142311140000041 
Figure BDA0005142311140000051
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of recycling and reuse, and more specifically to a method for recycling polyethylene terephthalate (PET). Background Art
[0002] Polyethylene terephthalate (PET) is a thermoplastic polyester made by copolymerizing terephthalic acid (TPA) and ethylene glycol (EG). It has excellent mechanical properties, low permeability, high transparency, non-toxicity and chemical stability. It is widely used in products such as bottles, fibers and films. It is the polyester plastic with the largest output. However, the PET molecular chain has a rigid benzene ring structure and strong intermolecular interactions, making it difficult to degrade in the natural environment. The accumulation of used PET products has caused huge pollution to the environment, so its recycling is particularly important, which can not only reduce resource consumption and environmental pollution, but also save energy and reduce raw material costs.
[0003] At present, the recycling of PET is mainly divided into physical recycling and chemical recycling. Physical recycling usually cleans and separates the waste PET through sorting and processing, and makes it into renewable particles or sheets. This method is simple to operate and low in cost. However, in the physical recycling process, the molecular chain of PET will be partially broken due to high-temperature melting and reprocessing, resulting in a decrease in molecular weight and reduced performance of the recycled product, which can only be used to manufacture low-end materials such as non-food packaging materials, short fibers and non-woven fabrics. Chemical recycling includes hydrolysis, methanolysis, glycolysis, and aminolysis, which can not only convert waste PET into new raw materials, but also further convert it into other high-value-added chemicals, thereby realizing efficient utilization of resources. Compared with physical recycling, chemical recycling can also effectively remove impurities and pollutants, improve the quality of recycled materials, and will not produce secondary pollution. The patent of CN114805766A discloses a method for preparing PBT from PBT and its waste PET polyester or / and PET-PBT mixed polyester, but the product needs to undergo multi-step processing, the process is complicated, and the energy consumption is high. Patent CN112441917A discloses a method for recovering terephthalate from waste PET, which also requires separation and purification to obtain the product. Therefore, a simpler method that does not require separation and purification is needed to recycle PET. Summary of the invention
[0004] Based on this, the object of the present invention is to provide a method for recycling polyethylene terephthalate (PET). The recycling method provided by the present invention uses organic acid adipic acid (AA), lactic acid (LA) and / or glycolic acid (GA) as catalysts to realize the hydrolysis reaction of polyethylene terephthalate (PET), and the products after the hydrolysis reaction do not need to be separated, and can all be used as subsequent reaction raw materials to participate in the polymerization reaction. By adding different monomers, different types of biodegradable copolyesters are prepared, and the conversion of non-degradable PET into biodegradable copolyesters is realized, which is of great significance for alleviating environmental pollution problems.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions:
[0006] The invention discloses a polyethylene terephthalate (PET) recycling method, which uses an organic acid as a catalyst to hydrolyze the PET, wherein the organic acid is selected from one or more of adipic acid, lactic acid and glycolic acid.
[0007] The PET in the present invention is selected from recycled materials of various molecular weights obtained from different sources, such as waste PET flat sheets, waste PET film materials, waste PET fibers, etc.
[0008] Further, in terms of mass percentage, the amount of the organic acid is 10-200wt% of the PET. Exemplarily, the amount of the catalyst can be 10wt%, 20wt%, 30wt%, 40wt%, 50wt%, 60wt%, 70wt%, 80wt%, 90wt%, 100wt%, 110wt%, 120wt%, 130wt%, 140wt%, 150wt%, 160wt%, 170wt%, 180wt%, 190wt%, 200wt% and the like of the PET, preferably in the range of 10-100wt%, more preferably 10-50wt%.
[0009] Further, the solvent used in the hydrolysis reaction is water;
[0010] In terms of mass percentage, the amount of water is 10-2000wt% of PET. For example, the amount of water is 10wt%, 50wt%, 100wt%, 150wt%, 200wt%, 250wt%, 300wt%, 350wt%, 400wt%, 450wt%, 500wt%, 550wt%, 600wt%, 650wt%, 700wt%, 750wt%, 80 ... 50wt%, 800wt%, 850wt%, 900wt%, 950wt%, 1000wt%, 1100wt%, 1200wt%, 1300wt%, 1400wt%, 1500wt%, 1600wt%, 1700wt%, 1800wt%, 1900wt%, 2000wt%, etc., preferably 100-1000wt%, more preferably 100-500wt%.
[0011] Furthermore, the temperature of the hydrolysis reaction is 50-250°C, preferably 180-220°C; the time of the hydrolysis reaction is 1-12 hours, so that the hydrolysis rate of PET in the hydrolysis reaction is 0-100%. When the hydrolysis rate of PET is 0, the mass of the solid does not change, but the molecular weight is significantly reduced, and oligomers are formed.
[0012] Furthermore, the hydrolysis reaction is carried out under closed conditions, for example, in a closed reactor.
[0013] Furthermore, the recycling method further comprises polymerizing the hydrolysis reaction product with additionally added monomers and a polymerization catalyst to prepare the biodegradable copolyester.
[0014] The hydrolysis reaction product used for repolymerization in the present invention can be either a monomer compound obtained after the hydrolysis reaction is completed, or an oligomer or a mixture of an oligomer and a monomer that has not been fully reacted. Regardless of the monomer, oligomer, or a mixture of the two, copolyester can be successfully polymerized. Therefore, the present invention can obtain biodegradable copolyester at a relatively lower energy consumption and in a shorter time.
[0015] Furthermore, the hydrolysis reaction product comprises oligomers and / or monomers of PET; preferably, the monomers are selected from terephthalic acid and / or ethylene glycol.
[0016] Further, the additionally added monomer is selected from terephthalic acid (TPA) and / or ethylene glycol (EG);
[0017] The polymerization catalyst is selected from one or more of antimony catalysts (such as antimony trioxide, ethylene glycol antimony and antimony acetate), germanium catalysts (such as germanium oxide), rare earth catalysts, and titanium catalysts (such as titanates, titanates, and titanium oxides), preferably titanate catalysts (such as tetrabutyl titanate TBT).
[0018] Furthermore, the polymerization reaction includes an esterification reaction and a polycondensation reaction which are performed in sequence.
[0019] Further, the polymerization comprises the following steps:
[0020] esterifying the hydrolysis reaction product with additionally added monomers and a polymerization catalyst;
[0021] The product of the esterification reaction is further subjected to a polycondensation reaction to obtain a biodegradable copolyester.
[0022] Furthermore, the conditions of the esterification reaction are: normal pressure, reaction temperature of 160-240°C, preferably 200-240°C; the conditions of the polycondensation reaction are: vacuum degree of 10-100 Pa, reaction temperature of 220-270°C, preferably 250-270°C.
[0023] Further, the molar ratio of the additionally added monomer terephthalic acid to the organic acid is 0.1-10, preferably 0.2-5. For example, the molar ratio of terephthalic acid to the organic acid can be 0.2, 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, etc.
[0024] Further, the molar ratio of the additionally added monomer ethylene glycol to the organic acid is 0.2-20, preferably 0.4-10. For example, the molar ratio of the ethylene glycol to the organic acid can be 0.4, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5, 10, etc.
[0025] Depending on the ratio of the additional monomers terephthalic acid and ethylene glycol, copolyesters with different molecular sequence structures can be prepared.
[0026] Furthermore, the polymerization catalyst accounts for 0.2-0.5wt% of the total acid in the polymerization system, preferably 0.4-0.5wt%. In the present invention, the total acid in the polymerization system refers to the sum of the amount of the added organic acid catalyst and the theoretical amount of TPA acid obtained after complete hydrolysis of PET.
[0027] Further, the biodegradable copolyester is prepared by the recycling method as described above. Exemplarily, the biodegradable copolyester is selected from one of the structures shown below:
[0028]
[0029] Among them, x is 1-10, y is 1-3, and z is 1-10.
[0030] The beneficial effects of the present invention are as follows:
[0031] 1. The recycling method provided by the present invention uses organic acids adipic acid (AA), lactic acid (LA) and / or glycolic acid (GA) as catalysts to realize the hydrolysis reaction of polyethylene terephthalate PET. The hydrolyzed product does not require any separation step and can be directly used for the next polymerization reaction, which greatly simplifies the process flow and reduces the production cost. In addition, the catalytic performance of the three organic acids is relatively high, so that the hydrolysis rate of PET is relatively high and the yield of the hydrolysis product TPA is also relatively high.
[0032] 2. Based on the hydrolysis reaction, the present invention mixes the hydrolysis product with additionally added different monomers, and sequentially completes the two-step reaction of esterification and polycondensation under the action of a polymerization catalyst to prepare copolyesters with different properties, thereby expanding the scope of application. At the same time, the prepared copolyesters are biodegradable, realizing the conversion of non-degradable PET into biodegradable copolyesters, which is of great significance for alleviating environmental pollution problems. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] The specific implementation modes of the present invention will be further described in detail below in conjunction with the accompanying drawings.
[0034] Figure 1 The FTIR spectrum of the hydrolysis product TPA in Example 1 is shown.
[0035] Figure 2 The hydrolysis product TPA in Example 1 is shown 1 H NMR spectrum. DETAILED DESCRIPTION
[0036] In order to more clearly illustrate the present invention, the present invention is further described below in conjunction with preferred embodiments and accompanying drawings. Similar components in the accompanying drawings are represented by the same reference numerals. It should be understood by those skilled in the art that the content specifically described below is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.
[0037] The structures of the hydrolyzed products were characterized using FTIR (FTIR-6800, Jasco, Japan) in the wavenumber range of 3500–600 cm -1 , the instrument resolution is 0.1cm -1 .
[0038] use 1 The structures of the hydrolyzed products were analyzed by H NMR (Avance 400, Bruker, Germany) in deuterated dimethyl sulfoxide (DMSO).
[0039] GPC (e2695, Waters, USA) was used to test the molecular weight and distribution of the polymer, with chloroform and o-chlorophenol as a mixed solvent, chloroform as the mobile phase, and PMMA as the reference substance.
[0040] Example 1
[0041] LA catalyzes the hydrolysis of PET:
[0042] PET particles (1.0 g), a certain amount of LA and water were added to a 50 mL reactor, heated and stirred at a certain temperature for a certain time, and the stirring speed was 25 rpm. After the reaction was completed, the reactor was naturally cooled to room temperature, the reaction liquid was filtered, and the remaining solid 1 and filtrate 1 were collected respectively. The remaining solid 1 was placed in a NaOH solution for reaction for a period of time, and then filtered again, and the remaining solid 2 (i.e., unreacted PET) and filtrate 2 were collected. The remaining solid 2 was washed three times with deionized water and dried in a vacuum oven at 60°C for 12 hours until constant weight. H2SO4 was added to the filtrate 2, filtered, and the precipitated remaining solid 3 (i.e., product TPA) was collected and dried in a vacuum oven at 60°C for 12 hours until constant weight. The hydrolysis rate of PET was calculated using formula (1), and the yield of product TPA was calculated using formula (2). The specific product results under different hydrolysis conditions are shown in Table 1.
[0043] PET hydrolysis rate (%) = (m0-m1) × 100 / m0(1)
[0044] Where m0 is the mass of the initial PET and m1 is the mass of the remaining solid 2.
[0045] TPA yield (%) = m a ×100 / m b (2)
[0046] Among them, m a is the mass of the remaining solid 3, m b is the theoretical mass of TPA that can be obtained by complete hydrolysis of PET.
[0047] Table 1 Product results under different hydrolysis reaction conditions
[0048]
[0049]
[0050] Note: The amounts of LA and water in Table 1 are expressed as a percentage by mass of LA or water relative to PET.
[0051] From the data in Table 1, we can see that LA has a significant promoting effect on the hydrolysis of PET. After adding LA, the hydrolysis rate of PET and the yield of product TPA are significantly improved. This is mainly because the H +The hydrolysis of PET was promoted. By adjusting factors such as temperature, reaction time, and catalyst dosage, the degree of hydrolysis of PET can be controlled to obtain oligomers and monomers. After optimizing the reaction conditions, the best reaction conditions were determined to be a hydrolysis temperature of 200°C, a hydrolysis reaction time of 5h, an LA dosage of 100wt%, and a water dosage of 300wt%. Under these conditions, the hydrolysis rate of PET was 100%, and the yield of the product TPA was 81.3%.
[0052] Figure 1 The FTIR spectrum of the hydrolysis product TPA in Example 1 is shown. Figure 2 The hydrolyzate TRA in Example 1 is shown in FIG. 1 HNMR spectrum. Figure 1 and Figure 2 It was found that TPA was obtained by the hydrolysis reaction.
[0053] Example 2
[0054] PET plastic bottle fragments (1.0 g), LA (1.0 g) and water (3.0 g) were added to a 50 mL reactor, heated and stirred at 200°C for 5 h, and the stirring speed was 25 rpm. After the reaction was completed, referring to the yield calculation method of Example 1, it was determined that the hydrolysis rate of the PET plastic bottle was 100%, and the yield of the product TPA was 79.3%. After comparing with the results of Example 1, it was found that under the same process conditions, the hydrolysis results of PET from different sources were basically the same.
[0055] Embodiment 3-5
[0056] LA catalyzes the hydrolysis of PET, and the hydrolysis product is polymerized to prepare PETL copolyester:
[0057] Hydrolysis: PET particles (50.0 g), LA (50.0 g) and water (150.0 g) were added to a 1.2 L reactor, heated and stirred at 200 °C for a period of time, and the stirring speed was 25 rpm. After the reaction was completed, the reactor was cooled naturally to room temperature, and all the products were added to a 500 mL three-necked flask.
[0058] Polymerization: TPA (141.4 g), EG (121.8 g) and polymerization catalyst TBT (1.17 g) were added to a three-necked flask, and the three-necked flask was placed in an oil bath equipped with an overhead stirrer at a stirring rate of 450 rpm. Subsequently, the reaction was carried out at 200-240°C for about 5-7 hours until the esterification reaction was completed and stopped. The pressure of the reaction system was reduced to below 100 Pa, and the temperature of the oil bath was raised to 250°C for polycondensation. The polycondensation reaction lasted for 3-4 hours. When the viscosity of the polymer was significantly increased and the torque of the stirring device reached 30 N·cm, the reaction was considered to have reached the end point. The time of the hydrolysis reaction and the molecular weight of the final product PETL are shown in Table 2.
[0059] Table 2 Molecular weight of final product PETL under different conditions
[0060]
[0061] Example 6
[0062] GA catalyzes the hydrolysis of PET:
[0063] PET particles (1.0 g), a certain amount of GA and water were added to a 50 mL reactor, heated and stirred at a certain temperature for a certain time, and the stirring speed was 25 rpm. After the reaction was completed, the reactor was naturally cooled to 60 ° C, the reaction liquid was filtered, and the remaining solid 1 and filtrate 1 were collected respectively. The remaining solid 1 was placed in a NaOH solution for reaction for a period of time, and then filtered again, and the remaining solid 2 (i.e., unreacted PET) and filtrate 2 were collected. The remaining solid 2 was washed three times with deionized water and dried in a vacuum oven at 60 ° C for 12 hours until constant weight. H2SO4 was added to the filtrate 2, and the precipitated remaining solid 3 (i.e., product TPA) was filtered and collected, and dried in a vacuum oven at 60 ° C for 12 hours until constant weight. The hydrolysis rate of PET was calculated using formula (1), and the yield of product TPA was calculated using formula (2). The specific product results under different hydrolysis conditions are shown in Table 3.
[0064] Table 3 Product results under different hydrolysis reaction conditions
[0065]
[0066] Note: The amounts of GA and water in Table 3 are expressed as mass percentages of GA or water relative to PET.
[0067] From the data in Table 3, it can be seen that GA has a significant promoting effect on the hydrolysis of PET. After adding GA, the hydrolysis rate of PET and the yield of product TPA are significantly improved. This is mainly because the H + The hydrolysis of PET is promoted. By adjusting factors such as temperature, reaction time, and catalyst dosage, the degree of hydrolysis of PET can be controlled to obtain oligomers and monomers.
[0068] Embodiment 7-9
[0069] GA catalyzes the hydrolysis of PET, and the hydrolysis product is polymerized to prepare PETG copolyester:
[0070] Hydrolysis: PET particles (50.0 g), GA (50.0 g) and water (150.0 g) were added to a 1.2 L reactor, heated and stirred at 200 ° C for a certain period of time, and the stirring speed was 25 rpm. After the reaction was completed, the reactor was cooled naturally to room temperature, and all the products were added to a 500 mL three-necked flask.
[0071] Polymerization: TPA (175.4 g), EG (147.2 g) and polymerization catalyst TBT (1.34 g) were added to a three-necked flask, and the three-necked flask was placed in an oil bath equipped with an overhead stirrer at a stirring rate of 450 rpm. Subsequently, the reaction was carried out at 200-240°C for about 5-7 hours until the esterification reaction was completed and stopped. The pressure of the reaction system was reduced to below 100 Pa, and the temperature of the oil bath was raised to 250°C for polycondensation. The polycondensation reaction lasted for 3-4 hours. When the viscosity of the polymer was significantly increased and the torque of the stirring device reached 30 N·cm, the reaction was considered to have reached the end point. The time of the hydrolysis reaction and the molecular weight of the final product PETG are shown in Table 4.
[0072] Table 4 Molecular weight of final product PETG under different conditions
[0073]
[0074] Example 10
[0075] AA catalyzes the hydrolysis of PET:
[0076] PET particles (1.0 g), a certain amount of AA and water were added to a 50 mL reactor, heated and stirred at a certain temperature for a certain time, and the stirring speed was 25 rpm. After the reaction was completed, the reactor was naturally cooled to 60°C, the reaction liquid was filtered, and the remaining solid 1 and filtrate 1 were collected respectively. The remaining solid 1 was placed in a NaOH solution for reaction for a period of time, and then filtered again, and the remaining solid 2 (i.e., unreacted PET) and filtrate 2 were collected. The remaining solid 2 was washed three times with deionized water and dried in a vacuum oven at 60°C for 12 hours until constant weight. H2SO4 was added to the filtrate 2, and the precipitated remaining solid 3 (i.e., product TPA) was filtered and collected, and dried in a vacuum oven at 60°C for 12 hours until constant weight. The hydrolysis rate of PET was calculated using formula (1), and the yield of product TPA was calculated using formula (2). The specific product results under different hydrolysis conditions are shown in Table 5.
[0077] Table 5 Product results under different hydrolysis reaction conditions
[0078]
[0079] Note: The amounts of AA and water in Table 5 are expressed as a percentage by mass of AA or water relative to PET.
[0080] From the data in Table 5, it can be seen that AA has a significant promoting effect on the hydrolysis of PET. After adding AA, the hydrolysis rate of PET and the yield of product TPA are significantly improved. This is mainly because the H +The hydrolysis of PET is promoted. By adjusting factors such as temperature, reaction time, and catalyst dosage, the degree of hydrolysis of PET can be controlled to obtain oligomers and monomers.
[0081] Examples 11-13
[0082] AA catalyzes the hydrolysis of PET, and the hydrolysis product is polymerized to prepare PEAT copolyester:
[0083] Hydrolysis: PET particles (50.0 g), AA (50.0 g) and water (150.0 g) were added to a 1.2 L reactor, heated and stirred at 210 ° C for a certain period of time, and the stirring speed was 25 rpm. After the reaction was completed, the reactor was cooled naturally to room temperature, and all the products were added to a 500 mL three-necked flask.
[0084] Polymerization: TPA (13.6 g), EG (68.8 g) and polymerization catalyst TBT (0.53 g) were added to a three-necked flask, and the three-necked flask was placed in an oil bath equipped with an overhead stirrer at a stirring rate of 450 rpm. Subsequently, the reaction was carried out at 200-240°C for about 5-7 hours until the esterification reaction was completed and stopped. The pressure of the reaction system was reduced to below 100 Pa, and the temperature of the oil bath was raised to 250°C for polycondensation. The polycondensation reaction lasted for 3-4 hours. When the viscosity of the polymer increased significantly and the torque of the stirring device reached 30 N·cm, the reaction was considered to have reached the end point. The time of the hydrolysis reaction and the molecular weight of the final product PEAT are shown in Table 6.
[0085] Table 6 Molecular weight of the final product PEAT under different conditions
[0086]
[0087]
[0088] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.
Claims
1. A method for recycling polyethylene terephthalate (PET), characterized in that: The PET is hydrolyzed using an organic acid as a catalyst, wherein the organic acid is selected from one or more of adipic acid, lactic acid and glycolic acid.
2. The recycling method according to claim 1, characterized in that: Calculated by mass percentage, the amount of the organic acid used is 10-200wt% of PET, preferably 10-100wt%.
3. The recycling method according to claim 1, characterized in that: The solvent used in the hydrolysis reaction is water; Calculated by mass percentage, the amount of water used is 10-2000wt% of PET, preferably 100-1000wt%.
4. The recycling method according to claim 1, characterized in that: The temperature of the hydrolysis reaction is 50-250° C.; the time of the hydrolysis reaction is 1-12 hours, so that the hydrolysis rate of PET in the hydrolysis reaction is 0-100%.
5. The recycling method according to claim 1, characterized in that: The recycling method further comprises polymerizing the hydrolysis reaction product with additionally added monomers and a polymerization catalyst to prepare the biodegradable copolyester.
6. The recycling method according to claim 5, characterized in that: The hydrolysis reaction product includes oligomers and / or monomers of PET; Preferably, the monomer is selected from terephthalic acid and / or ethylene glycol.
7. The recycling method according to claim 5, characterized in that: The additional monomers are selected from terephthalic acid and / or ethylene glycol; The polymerization catalyst is selected from one or more of antimony catalysts, germanium catalysts, rare earth catalysts, and titanium catalysts, and is preferably a titanate catalyst.
8. The recycling method according to claim 5, characterized in that: The polymerization reaction includes esterification and polycondensation reactions carried out in sequence; Preferably, the conditions for the esterification reaction are: normal pressure, reaction temperature of 160-240°C; the conditions for the polycondensation reaction are: vacuum degree of 10-100 Pa, reaction temperature of 220-270°C.
9. The recycling method according to claim 7, characterized in that: The molar ratio of the additionally added monomer terephthalic acid to the organic acid is 0.1-10; the molar ratio of the additionally added monomer ethylene glycol to the organic acid is 0.2-20.
10. The recycling method according to claim 5, characterized in that: The biodegradable copolyester is selected from one of the structures shown below: Among them, x is 1-10, y is 1-3, and z is 1-10.
Citation Information
Patent Citations
Method for recovering terephthalate from waste PET
CN112441917A
Method for preparing PBT (Polybutylene Terephthalate) from PBT and waste PET (Polyethylene Terephthalate) polyester thereof or / and PET-PBT mixed polyester
CN114805766A
Method for catalyzing degradation of polyethylene glycol terephthalate waste
CN111777489A
Method for catalytically hydrolyzing waste PET plastic by using recyclable solid organic acid
CN113072739A
Method for hydrolyzing waste PET plastic by acid catalysis
CN113444284A
Cited By
Degradable copolyester / PBAT blended mulching film and preparation method thereof
CN121758923A
Polymer alloy material, master batch and application
CN121758924A
Copolyester-based degradable film bag and preparation method thereof
CN121798877A